Novel polyarylates containing aryl ether units: synthesis, characterization and properties. Issue 5 (20th September 2012) - Liu, Pengqing; Wu, Ting; Ye, Guangdou; Xu, Jianjun
Abstract: To improve the processability of the poly( p ‐hydroxybenzoic acid), copolyarylates containing m ‐aryl ether units were synthesized using p ‐acetoxybenzoic acid, 1, 4‐diacetoxybenzene and 1, 3‐bis(4'‐carboxyphenoxy)benzene by melt transesterification reaction. The structure and properties of these polyarylates were characterized using infrared spectra, differential scanning calorimetry, thermogravimetric analyses, wide‐angle X‐ray diffraction and polarized optical microscopy etc. The results showed that all polyarylates were semicrystalline materials and could form a thermotropic liquid crystalline intermediate state. As the content of aryl ether units increased, the crystallization and melting temperatures of the polyarylate decreased; meanwhile, the crystalline ability became lower. The introduction of the aryl ether could restrain the formation of a liquid crystalline structure and reduce the thermal stability to some extent. After solid state polymerization (SSP), the intrinsic viscosity, melting temperature, crystallinity and thermal stability of the polyarylate increased while the melting range narrowed. However, the SSP reaction might be accompanied by degradation and crosslinking. Abstract : A series of thermotropic liquid crystalline copolyarylates containing m‐aryl ether units were synthesized. The aryl ether could restrain the formation of liquid crystalline structure and reduce the thermal stability.